2021
DOI: 10.34172/jsums.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Radial extracorporeal shock wave therapy for Dupuytren’scontracture: a case report

Abstract: Dupuytren’s contracture (DC) is a fibro-proliferative disorder of palmar and digital fascia, which leads to contracture deformity of hand and consequent disability. There is not a satisfying method for management of the disease and standard invasive treatments such as collagenase injection and fasciectomy have high rates of failure and recurrence. Recently, focused extracorporeal shock wave therapy (ESWT) has been used successfully for reduction of pain and dysfunction in DC. We hypothesized that radial ESWT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Range of motion (ROM) improved post-ESWT in the four studies in which it was measured. 19,21,23,24 Taheri's et al, 23 single participant case report demonstrated an improvement in range of motion to 'normal extension' postintervention. The case series by Taheri et al, 24 demonstrated statistically significant improvement in the extension range up to 14 weeks post-intervention.…”
Section: Found Thatmentioning
confidence: 98%
See 2 more Smart Citations
“…Range of motion (ROM) improved post-ESWT in the four studies in which it was measured. 19,21,23,24 Taheri's et al, 23 single participant case report demonstrated an improvement in range of motion to 'normal extension' postintervention. The case series by Taheri et al, 24 demonstrated statistically significant improvement in the extension range up to 14 weeks post-intervention.…”
Section: Found Thatmentioning
confidence: 98%
“…Studies were published between 1966 and 2022, in North America (three), Asia (five), Africa (one), Australia (one), and Europe (seven). Six interventions were identified: Extracorporeal Shockwave Therapy, [17][18][19][20][21][22][23][24] Corticosteroid Injection, [25][26][27] Splinting, [28][29][30] Massage and Stretching, 21,31 Ultrasound Therapy, 32,33 Temperature Controlled High Energy Adjustable Laser. 21 All studies recruited participants with stage 1 and stage 2 DD without significant digital contractures (which would qualify for a higher Chiu and McFarlane 5 rating as per Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation